Elongation of the poly-γ-glutamate tail of F420 requires both domains of the F420:γ-glutamyl ligase (FbiB) of Mycobacterium tuberculosis - Bashiri, Ghader; Mohamed Rehan, Aisyah; Sreebhavan, Sreevalsan; Baker, Heather M.; Baker, Edward N.; Squire, Christopher J. (American Society for Biochemistry and Molecular Biology Inc., 2016)
Cofactor F420 is an electron carrier with a major role in the oxidoreductive reactions of Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB). A γ-glutamyl ligase catalyzes the final steps of the F420 biosynthesis pathway by successive additions of L-glutamate residues to F420-0, producing a poly-γ-glutamate tail. The enzyme responsible for this reaction in Archaea (CofE) comprises a single domain and produces F420-2 as the major species. The homologous Mtb enzyme, FbiB, is a two-domain protein and produces F420 with predominantly 5-7 L-glutamate residues in the poly-γ-glutamate tail. The N-terminal domain of FbiB is homologous to CofE with an annotated γ-glutamyl ligase activity, whereas the C-terminal domain has sequence similarity to an FMN-dependent family of nitroreductase enzymes. Here we demonstrate that full-length FbiB adds multiple L-glutamate residues to F420-0 in vitro to produce F420-5 after 24 hours; communication between the two domains is critical for full γ-glutamyl ligase activity. We also present crystal structures of the C-terminal domain of FbiB in apo, F420-0 and FMN bound states, displaying distinct sites for F420-0 and FMN ligands that partially overlap. Finally, we discuss the features of a full-length structural model produced by small angle X-ray scattering (SAXS) and its implications for the role of N- and C-terminal domains in catalysis.